Persistent organic pollutants and methoxylated polybrominated diphenyl ethers in different tissues of white-tailed eagles (Haliaeetus albicilla) from West Greenland - Jaspers, V L B; Sonne, C; Soler-Rodriguez, F; Boertmann, David; Dietz, Rune; Eens, M; Rasmussen, L M; Covaci, A (Environmental Pollution, 2013)
We investigated polychlorinated biphenyls (PCBs), organochlorine pesticides (e.g. dichlorodiphenyltrichloroethane (DDT)), polybrominated diphenyl ethers (PBDEs) and methoxylated PBDEs (MeO-PBDEs), in six matrices (muscle, liver, kidney, adipose, blood, preen oil) of 17 white-tailed eagles from West Greenland sampled between 1997 and 2009. High inter-individual variation in contamination was found (PCBs: 0.49-1500 μg/g lipid weight (lw), DDTs: 0.23-910 μg/g lw, PBDEs: 0.01-24 μg/g lw, MeO-PBDEs: 0.001-0.59 μg/g lw), mostly due to age-related differences and not to temporal trends. One adult female (age > 5 years) displayed PCB levels up to 1500 μg/g lw in liver, which is the highest concentration ever reported in Arctic wildlife. Muscle generally contained the highest median levels, while adipose tissue displayed the lowest median levels on a lipid basis. No significant differences were found among tissues for MeO-PBDEs. Remarkably, we found distinct correlations (0.62 ≤ r ≤ 0.98;